2019
DOI: 10.3390/ijms20123065
|View full text |Cite
|
Sign up to set email alerts
|

Post-Mortem Immunohistochemical Evidence of β2-Adrenergic Receptor Expression in the Adrenal Gland

Abstract: The evidence from post-mortem biochemical studies conducted on cortisol and catecholamines suggest that analysis of the adrenal gland could provide useful information about its role in human pathophysiology and the stress response. Authors designed an immunohistochemical study on the expression of the adrenal β2-adrenergic receptor (β2-AR), a receptor with high-affinity for catecholamines, with the aim to show which zones it is expressed in and how its expression differs in relation to the cause of death. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 52 publications
0
6
0
1
Order By: Relevance
“…Interestingly, some researchers suggested that the spleen and lymph nodes lymphocytic depletion could be partially attributable to an endogenous increase of cortisol secretion by the fasciculated zone of the adrenal gland appearing hyperplastic ( Lax et al, 2020 ), as previously reported for lymphopenia related to SARS-1 disease ( Chong et al, 2004 ; Panesar, 2008 ). Furthermore, the role of adrenal gland in sepsis is well established as part of an intrinsic neuroendocrine response to sepsis-related circulatory failure ( Cumming et al, 1988 ; Ventura Spagnolo et al, 2019a ; Ventura Spagnolo et al, 2019c ). On the contrary, other researchers observed an evident adrenal vascular damage, namely vascular necrosis and endothelial apoptosis, hypothesizing that adrenal insufficiency related to vasculopathy may contribute to the cytokine storm characterizing COVID-19 ( Iuga et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, some researchers suggested that the spleen and lymph nodes lymphocytic depletion could be partially attributable to an endogenous increase of cortisol secretion by the fasciculated zone of the adrenal gland appearing hyperplastic ( Lax et al, 2020 ), as previously reported for lymphopenia related to SARS-1 disease ( Chong et al, 2004 ; Panesar, 2008 ). Furthermore, the role of adrenal gland in sepsis is well established as part of an intrinsic neuroendocrine response to sepsis-related circulatory failure ( Cumming et al, 1988 ; Ventura Spagnolo et al, 2019a ; Ventura Spagnolo et al, 2019c ). On the contrary, other researchers observed an evident adrenal vascular damage, namely vascular necrosis and endothelial apoptosis, hypothesizing that adrenal insufficiency related to vasculopathy may contribute to the cytokine storm characterizing COVID-19 ( Iuga et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…We found a strong difference in anthropometric and biochemical parameters between karate athletes and non-athletes subjects. In particular, a better glycaemic and lipid profile in athletes confirm the beneficial effects of physical activity (Cavaliere et al, 2019;Francavilla et al, 2018;Spagnolo et al, 2019;Ventura et al, 2018;Mondello et al, 2018). Also, the higher Orexin-A serum levels in karate athletes compared non-athletes subjects show the cognitive response induced by physical activity.…”
Section: Discussionmentioning
confidence: 60%
“…Immunohistochemistry is a useful, simple, and repeatable post-mortem investigation providing effective findings for the assessment of several causes of death [ 65 , 66 , 67 ]. The spectrum of the molecules immunohistochemically tested for sepsis is wide, and includes cell–cell adhesion molecules, chemoattractant molecules, acute phase mediators, growth factors involved in angiogenesis, and pro-inflammatory cytokines.…”
Section: Discussionmentioning
confidence: 99%